Psychological wellness and health‐related stigma: a pilot study of an acceptance‐focused cognitive behavioural intervention for people with lung cancer. (23rd July 2014) - Chambers, S.K.; Morris, B.A.; Clutton, S.; Foley, E.; Giles, L.; Schofield, P.; O'Connell, D.; Dunn, J.
<x xml:space="preserve">Abstract</x> People with lung cancer experience health‐related stigma that is related to poorer psychosocial and quality of life outcomes. The present Phase 1 study applied mixed methods to test the acceptability of an acceptance‐focused cognitive behavioural intervention targeting stigma for this patient group. Fourteen lung cancer patients completed a 6‐week Psychological Wellness intervention with pre‐ and post‐test outcome measures of psychological and cancer‐specific distress, depression, health‐related stigma and quality of life. In‐depth interviews applying interpretative phenomenological analysis assessed participants' experiences of the intervention. Moderate to large improvements were observed in psychological (ηp2 = 0.182) and cancer‐specific distress (ηp2 = 0.056); depression (ηp2 = 0.621); health‐related stigma (ηp2 = 0.139). In contrast, quality of life declined (ηp2 = 0.023). The therapeutic relationship; self‐management of distress; and relationship support were highly valued aspects of the intervention. Barriers to intervention included avoidance and practical issues. The lung cancer patients who completed the Psychological Wellness intervention reported improvements in psychological outcomes and decreases in stigma in the face of declining quality of life with patients reporting personal benefit from their own perspectives. A randomised controlled trial is warranted to establish the effectiveness of this approach.